2005
DOI: 10.1111/j.1365-2958.2005.04859.x
|View full text |Cite
|
Sign up to set email alerts
|

Ng‐MIP, a surface‐exposed lipoprotein of Neisseria gonorrhoeae, has a peptidyl‐prolyl cis/trans isomerase (PPIase) activity and is involved in persistence in macrophages

Abstract: SummaryMacrophage infectivity potentiators (MIPs) are a family of surface-exposed virulence factors of intracellular microorganisms such as Legionella , Chlamydia and Trypanosoma . These proteins display peptidylprolyl cis / trans isomerase (PPIase) activity that is inhibited by immunosuppressants FK506 and rapamycin. Here we describe the identification and characterization in Neisseria gonorrhoeae of Ng-MIP, a surface-exposed lipoprotein with high homology to MIPs. The protein is an homodimer with rapamycinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
110
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(116 citation statements)
references
References 27 publications
3
110
0
1
Order By: Relevance
“…PA4370 encodes an insulin-cleaving metalloproteinase (IcmP) whose activity was detected in outer membrane protein fractions; however, these authors did not report the presence of a predicted lipoprotein signal peptide (3). PA3262 encodes a probable peptidyl-prolyl cis-trans isomerase with homology to MIP (macrophage infectivity potentiator), which is a surface-exposed, outer membrane lipoprotein in Neisseria and Chlamydia (9,14). Regions encoding the native promoters and entire open reading frames (lacking stop codons) of predicted lipoproteins PA4370 and PA3262 were cloned upstream of mCherry.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PA4370 encodes an insulin-cleaving metalloproteinase (IcmP) whose activity was detected in outer membrane protein fractions; however, these authors did not report the presence of a predicted lipoprotein signal peptide (3). PA3262 encodes a probable peptidyl-prolyl cis-trans isomerase with homology to MIP (macrophage infectivity potentiator), which is a surface-exposed, outer membrane lipoprotein in Neisseria and Chlamydia (9,14). Regions encoding the native promoters and entire open reading frames (lacking stop codons) of predicted lipoproteins PA4370 and PA3262 were cloned upstream of mCherry.…”
Section: Resultsmentioning
confidence: 99%
“…Three fatty acids are attached to the N-terminal cysteine residue that immediately follows the cleavage site of lipoprotein signal peptides (13). The lipids integrate into the periplasm-facing leaflet of either membrane, leaving most lipoproteins exposed to the periplasm (13), although some lipoproteins are surface exposed (9,16). We have previously used fluorescent microscopy to visualize red fluorescent lipoproteins (lipoRFPs) directly in both the outer and inner membranes of Escherichia coli and other Enterobacteriaceae (10).…”
mentioning
confidence: 99%
“…The remaining glycoproteins include a peptidyl prolyl-isomerase (Ng1225), 2 solute-binding proteins associated with ABC transport systems (Ng0372 and Ng1494), and 2 lipoproteins of unknown function (Ng1043 and Ng2139). We further note that with the exceptions of PilE as well as Ng1225 and Ng2139 [for which evidence for surface exposure exists (24,25)], the glycoproteins are predicted to function in the periplasmic compartment, although their precise sites of localization await confirmation.…”
Section: N a A S G T A S A Pmentioning
confidence: 99%
“…Proteomic studies carried out in our laboratory identified the high abundance of a 29-kDa meningococcal MIP protein (the product of gene NMB1567, NEIS1487) in the OM (20). It has been also reported that the gonococcal homologue Neisseria gonorrhoeae macrophage infectivity potentiator (Ng-MIP) was a surface-exposed lipoprotein in N. gonorrhoeae (21). We showed in a previous study (22) that MIP is highly conserved, and in a collection of well-characterized meningococcal isolates (differing in serogroup, serotype, and serosubtype), isolated from carriers or patients, we found only three distinct MIP sequence types (designated I, II, and III).…”
mentioning
confidence: 99%